PERAN GURU BK DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA YANG KECANDUAN SMARTPHONE MELALUI LAYANAN BIMBINGAN KELOMPOK - Muhammad Buchori Ibrahim (Al-Mursyid : Jurnal Ikatan Alumni Bimbingan dan Konseling Islam (IKABKI), 2019)
This study aims to describe the role of BK teacher in increasing the motivation for learning students who are smartphone addicted through group guidance services. This study used qualitative analysis and used the subject called an informer, that is the principal, BK teacher, teachers and the students of 3rd grade of MAN Batu Bara determined by using purposive sampling it is choice of samples by considering that an informant who understands, knows, and feels firsthand the issues that are occurring. This study shows that the role of BK teacher conducted by a group guidance service that the BK teacher has been given to students of MAN Batu Bara systematically and continually makes positive and effective changes for increasing of student's learning motivation in smartphone addiction, the student who originally used a smartphone to just play games, social media and browsing are now being used to increase the learning motivations by using various learning applications, learning self through online videos and subscriptions with online learning guide such as www.quipper.com and www.ruangguru.com. Keywords: role of BK teacher, student learning motivation for smartphone addicted.